Transformations of the American hero in the US media discourse - Svitlana Lyubymova (Когниция, коммуникация, дискурс)
Abstract In the era of digital technologies, media has become a powerful tool of shaping worldview of people by means of sociocultural stereotypes. Formed in the process of evaluative categorization, sociocultural stereotypes represent simplified and conventional images of individuals and groups in media discourse. Affected by a range of factors, stereotypes undergo changes. Mass media play a particularly influential role in this process. The prominent figure of the US media landscape is ideologically charged stereotype of the American hero that embodies nationally significant ideas of freedom, individualism, and enterprise that lead to the accomplishment of a much-desired goal. I argue that the idealized cultural construct of the American hero, embodied in a sociocultural stereotype, is conceptualized through an image schema integrating foundational elements: PART–WHOLE–FORCE, SOURCE–PATH–GOAL. The WHOLE, representing the hero, comprises PARTS such as appearance, clothing, and behavior. FORCE signifies hero’s strength necessary to achieve the GOAL. SOURCE arises from one’s understanding, while the PATH involves overcoming adversities, culminating in success as the GOAL. This paper outlines transformations of the American hero stereotype in the US media discourse in diachronic perspective. Invariably virtuous, courageous, self-confident, purposeful, and hardworking, the American hero is inspirational and idealized image that takes on different forms due to changes of historical context. In different periods, the American hero is represented by a first settler, a cowboy, a ranger, a scientist. This stereotype functions as a model pattern for evaluating individuals and social groups. While the portrayal of the American hero in media discourse adapts to changing contexts, his image schema remains invariable.